Audit of Pediatric Transfusion Practices in a Tertiary Care Hospital: Correspondence - Aydin, Mustafa; Deveci, Ugur; Orman, Aysen; Taskin, Erdal; Kilic, Mehmet (All India Inst Medical Sciences, 2016)
[Abstract Not Available]
Keywords: Exchange-Transfusion; Blood